Expanding the HCI Agenda in Healthcare - KANE, BRIDGET; LUZ, SATURNINO (IEEE, 2014)
Designing technology for use in healthcare, and its evaluation in the healthcare setting, deserves special attention because of the nature of the special context of use. Biological hazards and the risk of infection, issues of privacy and security, system response times, as well as human factors and patient safety are identified as areas deserving of special attention. We give examples and quote from clinician interviews for illustration, and we argue that increased focus from the HCI community on these areas will bring tangible benefits of health information systems to healthcare staff, and ultimately improve patient services.
27th International Symposium on Computer Based Medical Systems
PUBLISHED
New York, USA
Keywords: Intelligent Content & Communications; HUMAN COMPUTER INTERACTION; Human-Computer Interaction